Hubungan Self Efficacy dengan Perilaku Pemeriksaan Keluarga Kontak Tuberkulosis di Kabupaten Pamekasan - Ahmadi, Ahmadi (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2018)
Tuberculosis is currently a problem for almost all countries. Even though various efforts have been made but until now no country in the world has escaped disease. Transmission of the disease due to Mycobacterium tuberculosis is easily transmitted, because of the entry of germs from the body only through the air. The study was carried out with observational techniques. The location of this study was conducted in Pamekasan Regency with the collection of research data from June 2017 to August 2017 using 379 samples. Data was taken directly to the research subjects using questionnaire sheets on all respondents who met the research criteria. Pearson Chi-Square test results show that the value of p = 0,000 is smaller than Î± = 0.05 so it is concluded that there is a significant relationship between Self Efficacy and the behavior of tuberculosis examination in Pamekasan RegencyÂ Keywords: Self Efficacy, Family Contact, Tuberculosis